Depression of Tissue Plasminogen Activator (t-PA) Activity and Rise of t-PA Inhibition and Acute Phase Reactants in Blood of Patients with Acute Myocardial Infarction (AMI) - Gram, Jørgen; Kluft, Cornelis; Jespersen, Jørgen (Thrombosis and Haemostasis, 1987)
We determined during the acute stage of myocardial infarction selected fibrinolysis variables (tissue-type plasminogen activator, intrinsic plasminogen activators, tissue-type plasminogen activator inhibition, C1-inactivator) and relatedthe observed changes to changes in two acute phase reactants (C-reactive protein, fibrinogen). Acute myocardial injury induce significant increases in blood of tissue-type plasminogen activator inhibition (day one, p <0.05), C-reactive protein (day three, p <0.01), fibrinogen (day six, p <0.01), and C1-inactivator (day eight, p <0.01). Tissue-type plasminogen activator activity measured as C1-inactivator resistant fibrinolytic activity showed a minimum day two after the acute attack (p <0.01), whereas plasminogen activator activities arising from the intrinsic system of fibrinolysis remained constant. The observed changes did not parallel the occurrence of deep vein thrombosis indicated by a positive Tc-plasmin test (41% of the patients).
Keywords: Acute myocardial infarction; Acute phase reactants; Fibrinolysis